Establishment and Mechanism Study of a Primary Ovarian Insufficiency Mouse Model Using Lipopolysaccharide - Si-Ji Lv; Shu-Hui Hou; Lei Gan; Jing Sun (Analytical Cellular Pathology)
This study is aimed at establishing a lipopolysaccharide- (LPS-) induced primary ovarian insufficiency (POI) mouse model and investigating the underlying mechanism. C57BL/6N female mice were intraperitoneally injected with low-dose LPS (0.5 mg/kg) once daily for 14 days, high-dose LPS (2.5 mg/kg) twice weekly for 2 weeks, or cyclophosphamide (CTX; 150 mg/kg) once weekly for 2 weeks. Ovarian function was assessed by measuring the length of estrous cycle, the number of primordial follicles, and the levels of serum hormones. Expression and production of interleukin 1β (IL-1β) were determined to evaluate ovarian inflammation. Histopathological examination was performed to examine ovarian fibrosis. TUNEL assay was carried out to evaluate granulosa cell apoptosis. Western blotting was performed to measure the levels of inflammation-, fibrosis-, and apoptosis-related proteins in the mouse ovaries. Like CTX, both low- and high-dose LPS significantly impaired ovarian functions in mice, as evidenced by extended lengths of estrous cycles, reduced counts of primordial follicles, and alterations in the levels of serum hormones. Also, LPS promoted granulosa cell apoptosis and ovarian fibrosis in mice. However, LPS but not CTX promoted IL-1β expression and production in mice. Moreover, LPS but not CTX enhanced TLR, p-p65, p65, and MyD88 expression in mouse ovaries, suggesting that LPS differs from CTX in triggering ovarian inflammation. In general, continuous low-dose LPS stimulation was less potent than high-dose LPS to affect the ovarian functions. In conclusion, LPS may induce ovarian inflammation, fibrosis, and granulosa cell apoptosis and can be used to establish a POI model in mice.